Macro-Fiscal Implications of Adaptation to Climate Change - Aligishiev, Zamid (Staff Climate Notes; Staff Climate Note ;, 2022)
Adaptation to climate change is an integral part of sustainable development and a necessity for advanced and developing economies alike. How can adaptation be planned for and mainstreamed into fiscal policy? Setting up inclusive coordination mechanisms and strengthening legal foundations to incorporate climate change can be a prerequisite. This Note identifies four building blocks: 1. Taking stock of present and future climate risks, identifying knowledge and capacity gaps, and establishing guidance for next steps. 2. Developing adaptation solutions. This block can be guided by extending the IMF three-pillar disaster resilience strategy to address changes in both extreme and average weather and would cover the prevention of risks, the alleviation of residual risks, and macro-fiscal resilience. 3. Mainstreaming these solutions into government operations. This requires strengthening public financial management institutions by factoring climate risks and adaptation plans into budgets and macro-frameworks, and in the management of public investment, assets and liabilities. 4. Providing for transparent evaluations to inform future plans. This involves continually monitoring progress and regularly updating adaptation plans.